Family history of psoriasis and recent infectious disease are risk factors for the first episode of acute guttate psoriasis - Naqqash, Shahzana; Tameez-ud-deen, Dr.; Naqqash, Shahid; Butt, Abdul Quddus (Journal of Pakistan Association of Dermatologists, 2017)
Background Psoriasis is a heterogeneous disease in its clinical expression. Both genetic and environmental factors are thought to contribute to the pathogenesis. The association of guttate psoriasis with streptococcal pharyngitis is well accepted. The association of other risk factors is less well-defined. Objectives The aim of this study was to estimate the risk for guttate psoriasis with recent infections and to explore other potential risk factors like family history of psoriasis. Patients and methods This was a case-control study. Cases were patients with the first diagnosis ever of acute guttate psoriasis. Controls were patients newly diagnosed as having dermatologic conditions other than psoriasis and seen in the same outpatient services as the cases. Inclusion of cases and controls was restricted to patients up to 18 years of age. A total 35 cases (median age, 8 years) and 150 controls (median age, 12Â½ years) were included in the analysis. Results A significant difference was observed for a family history of psoriasis. 45.7% of patients with guttate psoriasis gave a family history of psoriasis in their first-degree relatives. The risk of psoriasis was also increased in subjects who reported a history of a recent infectious episode. The analysis by individual diagnosis pointed to acute pharyngitis as the disease with the strongest association. Twenty-seven patients (77.1%) gave a history of sore throat preceding the onset of guttate psoriasis. All of them had a throat swab performed, of these 20 had normal flora cultured. Only 6 had a positive culture and in these cases Lancefield group C ÃŸ-hemolytic streptococci were isolated. ASO titer was raised in 21 (60%) patients of guttate psoriasis . Conclusion The study confirmed that recent pharyngeal infection is a risk factor for guttate psoriasis. It also documented the strong association between guttate psoriasis and a family history of psoriasis